COMPARATIVE STUDY OF OIL RECOVERY IMPROVEMENT BY STERILIZATION PROCESS USING FIREWOOD AND ELECTRICITY (Nigerian Journal of Technology, 2020)
This study presents a palm fruits sterilization unit that was designed for firewood and electricity independently as sources of energy and its performance was evaluated. 2kg of palm fruit at 100 oC for 30, 45, 60, 75, 90, 105 and 120 minutes using steam generated from electricity was evaluated. The yield of the palm fruits was also evaluated at 100 oC for 30, 45, 60, 75, 90, 105 and 120 minutes using firewood to cook palm fruits directly in water. Further laboratory experiment was conducted to investigate the quality of oil obtained from fresh palm fruits cooked with steam and fresh palm fruits cooked in water. The maximum oil fluid recovery percentage at 100 oC for 120 minutes sterilization time using electricity energy source and firewood energy source were 27.1 and 26.0 % respectively. The experimental result shows that at 100 oC and 90 minutes of sterilization using firewood and electricity, oil released from the digested fibre accounted for 46 % (111.33 g) and 54 % (130.5 g) of the total oil content respectively. The free fatty acid ,content peroxide value and moisture content of the oil sample cooked with steam and in water at 100 oC for 90 minutes were 3.9 %, 8.5 (O2/kg), 0.11 % and 4.4 %, 10.3 (O2/kg), 5.5 % respectively. The boiler efficiency of 99.5% was achieved for the unit. http://dx.doi.org/10.4314/njt.v39i3.24